Fruit pests of plum plantations of the Right-Bank Forest-Steppe of Ukraine and efficiency of protection - V. Filyov; L. Іurуk; N. Krikun (Карантин і захист рослин)
Goal. To determine the technical effectiveness of pesticides of different origin against fruit-damaging pests of plum in the conditions of the Right-Bank Forest-Steppe of Ukraine.